Anterior Cruciate Ligament Rupture Associated with Cardiomyopathy in Three Cats - Janssens, L. A. A.; Janssens, G. O.; Janssens, D. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
Over a period of 14 years, three cats with anterior cruciate ligament (ACL) rupture were seen in our practice. In all, the rupture had occurred without a history of previous trauma. All were treated surgically. All died within a period of 14 days. The reason of death was in all cases cardiomyopathy. We now suggest that cats with rupture of the anterior cruciate ligament undergo an electrocardiographic recording and eventually an thoracic radiography before surgery is considered. We also suggest that cats with ACL rupture should preferably be treated conservatively.
Keywords: Cardiomyopathy; cats; anterior cruciate ligament rupture